ANALYSIS OF FINANCIAL PERFORMANCE OF POLEWALI VILLAGE FUND ALLOCATION MANAGEMENT, SUPPA DISTRICT, PINRANG REGENCY - Nurcaya, Nurcaya; Arfianty, Arfianty; Andi AR (DECISION : Jurnal Ekonomi dan Bisnis, 2023)
The research entitled Financial Performance Analysis of Village Fund Allocation Management in Polewali Village, Suppa District, Pinrang Regency. The purpose of this study is to analyze the form of fund allocation in Polewali Village and analyze the financial performance of financial management in improving village financial performance in Polewali Village. The type of research used is qualitative research to reveal the results of research descriptively. The focus of this research is intended to limit the results of empirical studies while limiting research to relevant matters. This research focused on the village fund budget management strategy in Polewali Village. Based on the explanation above, the data analysis techniques applied include three things, namely as follows: data reduction, data presentation and conclusions, and data verification. The results in this study are financial management carried out by Polewali Village in improving financial performance, namely the suitability of village fund financial performance in Polewali Village, Suppa District by using economic standards including carrying out village fund budget planning, implementing village financial performance. The Fund Budget reports the financial performance of the Village Fund Budget, making accountable the financial performance of the Village Fund Budget.